2018
DOI: 10.1177/1538574418819540
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Complications of New-Onset Complicated Type B Aortic Dissection After Endovascular Abdominal Aortic Aneurysm Repair: Report of 2 Cases and Literature Review

Abstract: New-onset antegrade Stanford type B aortic dissection (TBAD) after endovascular aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA) is rare. The extension of aortic dissection leads to various symptoms and affects the stent graft. Moreover, various symptoms may arise owing to a stent graft being present. We describe 2 cases of complicated acute TBAD occurring after EVAR, which were ultimately fatal. The case in which rupture occurred could not be treated and the patient died. In another case with bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Conversely, most cases (17/20) of TBAD during the midterm postoperative period (2 weeks after EVAR) were complicated, including malperfusion, aneurysm expansion, or aneurysm rupture, which might require surgical or endovascular interventions. 2,3,6,8,10) Majority of these complicated cases had antegrade dissection from the distal arch of the left subclavian artery to the proximal stent graft. Finally, the prognosis is different depending on the onset of TBAD after EVAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, most cases (17/20) of TBAD during the midterm postoperative period (2 weeks after EVAR) were complicated, including malperfusion, aneurysm expansion, or aneurysm rupture, which might require surgical or endovascular interventions. 2,3,6,8,10) Majority of these complicated cases had antegrade dissection from the distal arch of the left subclavian artery to the proximal stent graft. Finally, the prognosis is different depending on the onset of TBAD after EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Nomura et al reviewed 10 cases of spontaneous complicated TBAD after EVAR and found that collapse of stent graft and thrombosis occurred in 80% of these cases and suggested that they are fatal because the reentry is not formed by the presence of the stent graft. 2)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…at the origin of the left subclavian artery. Among 12 cases, 2 resulted in immediate mortality following rupture [ 4 ]. Of the 5 patients who underwent emergent TEVAR, 1 succumbed to non-disease-related intracranial haemorrhage [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 5 patients who underwent emergent TEVAR, 1 succumbed to non-disease-related intracranial haemorrhage [ 5 ]. Furthermore, early mortality due to the necrosis of the visceral organs occurred in 2 of the 5 patients who underwent EAB [ 4 ]. Lower-extremity amputation due to intraoperative rupture was performed in 1 patient [ 3 ].…”
Section: Discussionmentioning
confidence: 99%